2017
DOI: 10.15343/0104-7809.20174103350358
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da qualidade do sono e fatores associados em pacientes diabéticos tipo 2

Abstract: ResumoAnalisar a qualidade do sono e possíveis fatores associados em pacientes diabéticos tipo 2. Estudo descritivo transversal e quantitativo com 74 pacientes. Foram utilizados o Índice de Qualidade de Sono de Pittsburgh (PSQI) para avaliação da qualidade do sono e um questionário com informações socioeconômicas e clínicas. As análises multivariadas foram conduzidas por meio de regressão logística. A maioria dos pacientes tinha 50 anos ou mais de idade (54,1%). Quase 80% tinham diagnóstico de hipertensão arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
1
0
0
1
Order By: Relevance
“…Comparing these results with those of the present study shows that the prevalence of poor sleep quality is even higher, which reinforces the problem related to sleep quality in patients with diabetes. In the Brazilian context, the lack of robust and reliable studies on the subject is evident, but a study carried out in Paraná with type 2 diabetic patients found a prevalence of 64.9% of poor sleep quality (21) , while another study reported a prevalence of 53.3% of poor sleep quality (22) , similar to that found in the present study.…”
Section: Discussionsupporting
confidence: 83%
“…Comparing these results with those of the present study shows that the prevalence of poor sleep quality is even higher, which reinforces the problem related to sleep quality in patients with diabetes. In the Brazilian context, the lack of robust and reliable studies on the subject is evident, but a study carried out in Paraná with type 2 diabetic patients found a prevalence of 64.9% of poor sleep quality (21) , while another study reported a prevalence of 53.3% of poor sleep quality (22) , similar to that found in the present study.…”
Section: Discussionsupporting
confidence: 83%
“…Ao comparar esses resultados com os do presente estudo, verifica-se que a prevalência de má qualidade do sono é ainda maior, o que reforça a problemática envolvendo a qualidade do sono em pacientes com diabetes. No contexto brasileiro, a escassez de estudos robustos e confiáveis sobre o tema é evidente, mas um estudo realizado no Paraná com pacientes diabéticos tipo 2 encontrou uma prevalência de 64,9% de má qualidade do sono (21) , enquanto outro estudo identificou uma prevalência de 53,3% de má qualidade do sono (22) , semelhante à encontrada no presente estudo.…”
Section: Discussionunclassified